The Impact of Oil Price Volatility, Gross Domestic Product, Foreign Direct Investment on Islamic Banking Investments: An Empirical Evidence of The United Arab Emirates - Tabash, Mosab I.; Khan, Samar H. (International Journal of Energy Economics and Policy, 2018)
The current paper examines the impact of Oil Price (OP) fluctuations on Islamic banking investments growth in the UAE. Besides, oil price, the study also uses other variables like Gross Domestic Product (GDP) and Foreign Direct Investment (FDI) to identify the determinants of the Islamic banking investments growth in the emerging economy, UAE. The study is based on econometric analysis with the help of annual time series data from 1990 to 2015 for the study variables. Stationary tests, Cointegration methods, Vector Error Correction Model (VECM), and Granger causality tests are used in the analysis. The major findings of the study revealed that oil prices have long-term and short-term relationships on the Islamic banking investments in the UAE. Our results explore the importance of oil price stabilization in enhancing growth and progress in the UAE economy. The Government of UAE should reform policies and procedures to minimize the effect of such volatility in oil prices which in turn leads to positive impacts on the UAE economy as well. Keywords: Oil Price, Volatility, FDI, GDP, Islamic investments, Growth, UAE. JEL Classifications: F21, F41, O16